O władcy i jego poddanych, czyli Gorgiasz 469 C według Seneki Młodszego - Budzanowska, Dominika (Civitas. Studia z filozofii polityki, 2011)
In Plato’s dialogue ‘Gorgias’, which is a polemic with rhetoric as an ability to choose the unfair, Socrates proves that it is better to experience the injustice rather than to cause it. A few centuries later, this idea was further exploited by a Roman Empire Stoic Lucius Annaeus Seneca, also called Seneca the Younger or Philosophus. The basic idea of Seneca’s political thought is hatred towards the tyranny and a simultaneous acceptance of a fair sovereign who can control his anger and look after his country. Through his work Seneca is encouraging a just life that is in accordance with god’s laws. For him, justice is the core for the functioning of a society. Seneca also claims that human relations should be based on natural reasoning rules.